2013
DOI: 10.1146/annurev-physiol-030212-183748
|View full text |Cite
|
Sign up to set email alerts
|

Phosphate Transporters and Their Function

Abstract: Plasma phosphate concentration is maintained within a relatively narrow range by control of renal reabsorption of filtered inorganic phosphate (P(i)). P(i) reabsorption is a transcellular process that occurs along the proximal tubule. P(i) flux at the apical (luminal) brush border membrane represents the rate-limiting step and is mediated by three Na(+)-dependent P(i) cotransporters (members of the SLC34 and SLC20 families). The putative proteins responsible for basolateral P(i) flux have not been identified. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
137
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 153 publications
(139 citation statements)
references
References 97 publications
0
137
0
2
Order By: Relevance
“…By contrast, linkage analyses have found that in humans, Npt2a and Npt2c may contribute equally to phosphate reabsorption (30,31). The importance of PiT-2 in the renal control of Pi in humans remains unclear (20).…”
Section: Renal Regulation Of Phosphate Balancementioning
confidence: 96%
See 1 more Smart Citation
“…By contrast, linkage analyses have found that in humans, Npt2a and Npt2c may contribute equally to phosphate reabsorption (30,31). The importance of PiT-2 in the renal control of Pi in humans remains unclear (20).…”
Section: Renal Regulation Of Phosphate Balancementioning
confidence: 96%
“…Within the body, the majority of phosphorus stores are in the bone. Although serum phosphate (Pi) levels constitute ,1% of total body phosphorus stores, maintenance of serum Pi within a relatively narrow range (2.5-4.5 mg/dl in adulthood) is crucial for several important cellular processes, including energy metabolism, bone formation, signal transduction, or as a constituent of phospholipids and nucleic acids (20). Maintenance of serum phosphate within the normal range depends on a complex interplay between absorption of phosphate in the gut, exchange with bone stores, shifts between intracellular and intravascular compartments, and renal excretion.…”
Section: Phosphorusmentioning
confidence: 99%
“…phosphate transport; Caco2BBE cells; Na ϩ -independent Pi uptake; phosphate absorption; small intestine; inorganic phosphate CONTROL of P i homeostasis is mediated by the coordinated activity of a complex set of physiological mechanisms acting on the rate of intestinal absorption, rate of renal excretion, and eventual mobilization of the bone reservoir. These mechanisms consist of hormones and nonhormonal events that act either acutely or slowly (chronically) to modulate the activity of plasma membrane P i transporters (2,4,23). The precision of P i homeostasis control is critical not only because of the extreme relevance of the physiological roles of P i in the organism (pH buffer, energy bonds, signal transduction, phospholipid composition, bone formation, etc.)…”
mentioning
confidence: 99%
“…Shaded bars on the top of the alignment indicate predicted transmembrane domains (numbered). Membrane-spanning domains (blue) and re-entrant domains (orange) were fitted using the amino acid sequence analysis program HMMTOP (41) and by comparisons with topological data from other Slc34a2 sequences (6,14,19). A motif reported to be responsible for pH-dependent transport (red overscore) is also highlighted (19).…”
Section: Discussionmentioning
confidence: 99%
“…The amino acid sequence of the hagfish Slc34a-like transporter was aligned with Slc34a2 protein sequences from other fish and mammalian species obtained from NCBI and Ensembl using the ClustalW2 analysis program (http://www.ebi.ac.uk/Tools/ msa/clustalw2/). Membrane-spanning domains and re-entrant domains were determined using HMMTOP (41) and by comparisons with topological data from other Slc34a2 sequences (6,14,19,42).…”
Section: Methodsmentioning
confidence: 99%